ESTRUS INDUCTION RESPONSE FOLLOWING HORMONE TREATMENT IN MURRAH BUFFALO - DHALKARI, S; SAHATPURE, S K; PATIL, A D; PATI, P; GAWANDE, A P (The Indian Journal of Animal Reproduction, 2022)
Eighteen anestrus Murrah buffalo were divided equally into three different groups comprising of 6 buffaloeach. One group received norgestomet ear implant for 7 days along with norgestomet and estradiol valerate (i.m.)on day 0. Another group received inj. buserelin acetate (i.m.) on day 0 along with a progesterone impregnatedintravaginal insert for 7 days. The remaining buffalo were kept as untreated control. Norgestomet-based andintravaginal progesterone-based treatment led to estrus induction in 50% and 83.3% buffalo, respectively.However, there was no difference (p>0.05) in time required for onset of estrus and duration of induced estrusbetween treatment groups. The intensity of estrus was better in intravaginal progesterone-treated buffalo. Insummary, intravaginal progesterone-based treatment had an edge over norgestomet ear implant treatment forinduction of estrus in anestrus Murrah buffalo.
Keywords: Anestrus; Buffalo; Estrus induction; Norgestomet; Progesterone